Light technology and its impact on contemporary plastic art The art of light as a model (Journal of the College of Basic Education, 2022)
In light of the authority of technology as one of the most important secretions from the era of modernity to the era after .. postmodernity. image dominance. Successive models of creative works appeared, following the developments of the era emanating from it. And electronic and technological techniques are an important part of their formations to achieve pleasant aesthetic experiences. It may be covered with digital worlds to get the greatest amount of communication and interaction with the new reality that carries the same aesthetic concepts, but it celebrates the technical age. On the other hand, a generation of cosmic reception appeared looking for that approach, chasing the moment and moment in the artwork that relies on electronic processors, and looking for dazzle in the new experiences and mechanisms that were employed to achieve an audiovisual image that adopts a relational formation with the media, communication and communication.